FUNGSI PENGAWASAN BADAN PERMUSYAWARATAN DESA DALAM PELAKSANAAN PEMBANGUNAN DESA DI KECAMATAN GALELA KABUPATEN HALMAHERA UTARA. - USMANY, Budiyarto; Dengo, Salmin; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: Law No. 6 of 2014 on the village of securing that one function of BPD is a supervisory institutionin the village. The purpose of this study was to determine how the oversight function of BPD in theimplementation of rural development in the district Galela North Halmahera.Research using qualitative, methods. Informants were taken from the elements associated with theimplementation of development in villages, the village government (village head), BPD, the villagecommunity institutions (LPM, PKK and others), and residents of rural communities. The totally number ofinformants there are as many as 12 informants.. data collection by interviewing techniques; while the dataanalysis using analytical techniques interactive model of Miles and Hubernann.Based on the results of the study it can be concluded that the supervisory function of BPD in theimplementation of rural development in the district Galela North Halmahera has been implemented fairlywell, but not maximum views of as many as fourteen dimensions of the implementation of the supervisoryfunction used in this study.Based on the conclusions of the research results it is necessary to put forward suggestions: (1) BPDshould strive to carry out oversight functions professionally and objectively without influence or interventionfrom the chief. (2) MRD should be people who have good skills in aspects of knowledge / education,experience, mental attitude, and have a commitment and integrity in running duties and functions assupervisory institutions in the village. (3) BPD should be supported by local villagers in performing its dutiesand functions; and therefore it must be good cooperation between the BPD and villagers.Keywords: supervision functions, BPD, the implementation of rural development.